Periodontitis and Subsequent Risk of Cataract: Results From Real-World Practice - Yeh, Li-Jen; Shen, Te-Chun; Sun, Kuo-Ting; Lin, Cheng-Li; Hsia, Ning-Yi (Frontiers in Medicine, 2022)
Background Periodontitis can lead to systemic inflammation and oxidative stress, contributing to the development of various diseases. Periodontitis could also be associated with several ocular diseases. Methods We conducted a retrospective population-based cohort study using the National Health Insurance Research Database of Taiwan to evaluate the risk of cataract in people with and without periodontitis. We established a periodontitis cohort and a non-periodontitis cohort, which included 359,254 individuals between 2000 and 2012. Age, gender, and enrolled year were matched. All participants were monitored until the end of 2013. Cox proportional hazard models were applied to estimate hazard ratios (HRs) and confidence intervals (CIs). Results Patients with periodontitis had a significantly higher risk to develop cataract than those without periodontitis [10.7 vs. 7.91 per 1000 person-years, crude HR = 1.35 (95% CI = 1.32–1.39), and adjusted HR = 1.33 (95% CI = 1.30–1.36)]. The significant levels remained the same after stratifying by age, gender, presence of comorbidity, and use of corticosteroid. In addition, we found that diabetes mellitus and hyperlipidemia were important promotive comorbidities for the development of cataract. Conclusion Patients with periodontitis have a higher risk of cataract development than those without periodontitis. Such patients may request frequent ocular health check-up. Further studies should be performed to confirm the association and to understand the mechanisms.